Hardship, coping, and joy: ACPs’ experiences of working through the COVID-19 pandemic - Emily Heavey; Melanie Rogers; Vanessa Taylor; Lihua Wu; Angela Windle (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This paper reports Advanced Clinical Practitioners’ (ACPs) experiences of working in the United Kingdom during the COVID-19 pandemic, specifically the factors that impacted their mental, emotional, and physical wellbeing. Methods The study presents qualitative data collected via two surveys in 2020 and 2021. Several survey questions elicited free-text responses, including a specific request for narratives. Narrative responses were thematically analysed and cross-referenced with non-narrative qualitative responses. Results Three factors contributed to poor wellbeing: a changing work environment and expectations; bearing witness to the impact of Covid on patients; and the risk of catching and spreading Covid. Three factors improved wellbeing, whether through mitigating these challenges or directly, in the absence of specific hardship. These factors were new working practices; support structures; and individual resilience and self-managed coping strategies. Conclusion This study expands research on professionals’ experiences of working through Covid to the under-researched experience of ACPs and demonstrates the intersecting and overlapping nature of factors contributing to poor and positive wellbeing. There are significant implications for stakeholders who need to consider the impact of future pandemics and opportunities for supporting and promoting wellbeing post-pandemic. The analysis also highlights the rich narrative data that can be collected using surveys.